2019
DOI: 10.25035/jade.01.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Parental Support, Sibling Influences and Family Dynamics across the Development of Canadian Interuniversity Student-Athletes

Abstract: A vast body of research focuses on the role of parents in athlete development; however, little is known about developmental influences of siblings. In general, family dynamics (i.e., patterns of relating or interacting among family members) have yet to be investigated in youth sport contexts. This study examines how family dynamics and the individual roles of parents and siblings influence the development of Canadian interuniversity student-athletes over time. Participants included four male and six female stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Student-athletes described the stable and dynamic forms of support shown to them both by their mother and father, and how the assistance was significant to and valued by them. The result in the study of [26] indicated that parents play an important role in athletic development throughout childhood and adolescence. Parental help according to [27], like bringing their child to a training session, supporting the competition, motivating them when discouraged, and sharing the child's success are perceived by young athletes as overwhelming.…”
Section: Discussionmentioning
confidence: 99%
“…Student-athletes described the stable and dynamic forms of support shown to them both by their mother and father, and how the assistance was significant to and valued by them. The result in the study of [26] indicated that parents play an important role in athletic development throughout childhood and adolescence. Parental help according to [27], like bringing their child to a training session, supporting the competition, motivating them when discouraged, and sharing the child's success are perceived by young athletes as overwhelming.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-sibling rivalry within sport is common, particularly closely spaced siblings as they both aspire to achieve superior athletic status (Davis & Meyer, 2008). This rivalry often motivates the athletic pursuits of younger siblings who look up to their older siblings with increased admiration and seek their approval (Côté, 1999;Lundy et al, 2019). Same sex siblings who participated in the same sport have disclosed that they can be highly critical of one another which can result in negative inter-sibling rivalry (Nelson & Strachan, 2017).…”
Section: Influences Within the Homementioning
confidence: 99%
“…Both interact in determining how the athlete's personality is formed, including in achieving high achievements [ [9] , [10] ]. In many studies, the environment in which individuals grow and develop such as the family environment and school environment is recognized to be very influential on the emergence of high-achieving individuals [ [11] , [12] , [13] ]. Even for athletes, the sports environment where there are coaches and teammates will certainly influence their success in achieving achievements [ 3 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%